Karakteristik infeksi virus dengue di RSUD Lewoleba Kabupaten Lembata pada periode Januari 2019 – Desember 2021 - Vennia Riskia Tristianti; Juliana Manurung; Rosalia Theodosia Daten Beyeng (Intisari Sains Medis, 2022)
Background: Dengue virus infection has become an international problem that has increased in the last three years. East Nusa Tenggara is always included in the top five provinces with the most cases of dengue, as well as Lembata Regency. Therefore, this study aims to determine the characteristics of dengue virus infection in pediatric patients in Lembata Regency. Methods: A retrospective descriptive study using a simple random sampling method on 81 children with dengue virus infection who were treated at Lewoleba General Hospital during January 2019 – December 2021. The data collected through medical records. Data analysis was performed with SPSS version 22 for Windows. Results: Dengue infections’ characteristics in Lewoleba General Hospital were male (60.5%), range from 5 – 10 years old (46.9%), with good nutritional status (63%). The most clinical symptoms were fever, which was mostly on day 5 accompanied by abdominal pain (76.5%), vomiting (75.3%), headache (49.4%), muscle pain (37%), spontaneous bleeding (25.9%), hepatomegaly (55.6%), and petechiae (33.3%). The length of stay is 3 – 5 days (53.1%). 55.6% patients had secondary infection, 30,9% had grade II dengue hemorrhagic fever, with leukopenia (<5000/µL) (49.4%) and trombositopenia (50,000 – 100,000/µL) (42%). All subjects went home recovered (100%). Conclusion: The characteristics of dengue virus infection in Lewoleba General Hospital mostly men aged 5-10 years, with good nutrition, had fever, abdominal pain, vomiting, headache, joint pain, spontaneous bleeding, hepatomegaly, and petechiae. Most dengue infections are secondary. The highest degree is grade II, laboratory findings showed leukopenia and thrombocytopenia.   Latar Belakang: Infeksi virus dengue telah menjadi masalah internasional yang mengalami peningkatan frekuensi dalam tiga tahun terakhir. Nusa Tenggara Timur selalu masuk dalam lima besar provinsi dengan kasus terbanyak infeksi virus dengue, demikian pula dengan Kabupaten Lembata. Oleh karena itu penelitian ini bertujuan untuk mengetahui karakteristik infeksi virus dengue pada pasien anak di Kabupaten Lembata. Metode: Penelitian dengan metode deskriptif retrospektif dengan pengambilan sampel acak terhadap 81 anak dengan infeksi virus dengue yang dirawat di RSUD Lewoleba periode Januari 2019 – Desember 2021. Data diambil melalui rekam medis pasien. Analisis data dilakukan dengan SPSS versi 22 untuk Windows. Hasil: Karakteristik infeksi dengue di RSUD Lewoleba terbanyak adalah laki-laki (60,5%), usia 5 – 10 tahun (46,9%), dengan status gizi baik (63%). Gejala klinis terbanyak adalah demam  pada hari ke-5, disertai dengan nyeri perut (76,5%), muntah (75,3%), nyeri kepala (49,4%), nyeri otot (37%), perdarahan spontan (25,9%), hepatomegali (55,6%), dan petechiae (33,3%). Lama hari rawat adalah 3 – 5 hari (53,1%). 55,6% pasien mengalami infeksi sekunder, 30,9% mengalami demam berdarah derajat II, dengan leukopenia (5.000/µL) (49,4%) serta trombositopenia (50.000 – 100.000 /µL) (42%). Seluruh subyek penelitian pulang dengan keadaan sembuh (100%). Kesimpulan: Karakteristik infeksi virus dengue di RSUD Lewoleba adalah lebih banyak mengenai laki-laki usia 5-10 tahun dengan gizi baik, disertai gejala demam, nyeri perut, muntah, nyeri kepala, nyeri sendi, perdarahan spontan, hepatomegali, petechiae. Infeksi dengue terbanyak adalah infeksi sekunder, infeksi terbanyak adalah derajat II, serta ditemukan adanya leukopenia dan trombositopenia.